Faktor Kerentanan Sosial terhadap Perubahan Iklim pada Masyarakat Rentan di Indonesia - Badikenita Br. Sitepu (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Climate change is a global phenomenon that is spreading its impacts unevenly across community groups. This study aims to describe the impacts of climate change on vulnerable communities and identify factors that shape their vulnerability. The method used is descriptive-analytical through a literature review and synthesis of findings from various related studies. The analysis focuses on three dimensions of vulnerability such as exposure, sensitivity, and adaptive capacity. The results of the study indicate that groups such as farmers, fishermen, and livestock breeders experience direct impacts in the form of decreased productivity due to changing climate patterns and extreme weather. Meanwhile, indigenous communities face threats to their livelihood systems and cultural identity due to ecosystem degradation. Poor communities, women, and children exhibit multiple vulnerabilities influenced by limited access to resources, basic services, and social protection. In general, vulnerability is shaped by high dependence on natural resources, economic constraints, and weak institutional support. From a climate justice perspective, inequality in the distribution of impacts and adaptive capacity is found, with vulnerable communities bearing a greater burden. Therefore, a more inclusive, contextual, and equitable policy approach is needed, taking into account the specific characteristics and needs of each community group in facing climate change.